Poligami menurut Nasr Hamid Abu Zayd: studi atas pengaruh pemikiran tafsir terhadap penetapan hukum - Cucu Surahman (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This article examines Nasr Abu Zayd’s (d. 2010) thought of tafsir and takes a close look at its implementation when he interprets “polygamy verses”. With library research method and content analysis, I conclude that Abu Zayd uses thematic method of interpretation, by using contextual analysis approach. This method is similar to Fazlur Rahman’s Double Movement method. Abu Zayd’s contextual interpretation theory (al-qira’ah al-siyaqiyyah) operates in the following steps; first, turn to the meaning (ma’na) of the text in its historical and cultural context (tarikhiyyat al-dalalah); and second, implement its significance (maghza) in contemporary context. Based on his contextual analysis (al-qira’ah al-siyaqiyyah) to polygamy verses, Abu Zayd concludes that polygamy is not the final purpose Islamic teaching (shari’ah al-Islamiyah). Polygamy is a temporal decision which is related to the very tight prerequisites. According to him, the significance (maghza) of the Qur’an text talking about polygamy is however justice and equality. Otherwise, Abu Zayd says that the implicit (maskut ‘anhu) final purpose of the revelation of “polygamy related-verses” are monogamy.